2021
DOI: 10.1002/int.22732
|View full text |Cite
|
Sign up to set email alerts
|

Predictive intelligence using ANFIS‐induced OWAWA for complex stock market prediction

Abstract: Traditional time series prediction methods are unable to handle the complex nonlinear relationship of a large data set. Most of the existing techniques are unable to manage multiple dimensions of a data set, due to which the computational complexity escalates with the increasing size of a data set. Many machine learning (ML) methods are unable to handle known unknown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…By obtaining a minimum MAPE value of 0.01398, the proposed methods outperformed various existing studies (e.g. Ahmar and Del Val, 2020;Hussain et al, 2021;Albahli et al, 2022;Bathla et al, 2022). The results reveal that the MAPE value is dependent on the variations in sector stock prices over the testing period.…”
Section: Resultsmentioning
confidence: 73%
“…By obtaining a minimum MAPE value of 0.01398, the proposed methods outperformed various existing studies (e.g. Ahmar and Del Val, 2020;Hussain et al, 2021;Albahli et al, 2022;Bathla et al, 2022). The results reveal that the MAPE value is dependent on the variations in sector stock prices over the testing period.…”
Section: Resultsmentioning
confidence: 73%
“…Moreover, Chan and Chong ( 134 ) and Teo et al ( 135 ) reported that the ANN is utilized to identify complex linear and non-linear relationships. Although recent studies suggested that the ANN is not enough to handle a complex nonlinear relationship ( 136 , 137 ). Nevertheless, the ANN approach give better results than conventional prediction methods ( 137 ) and is more precise than the usual regression strategy in terms of prediction ( 82 , 138 ).…”
Section: Methodsmentioning
confidence: 99%
“…So, the stock market analysis model should address that we should elect the suitable algorithms which are less prone to the more generic conditions and end up with some 60% to 75% predictions. Some of the researchers [31]- [39] employed the techniques of SVM and KNN the authors provided the accuracy ranging from 65% to 81% and in the work [40]. While these works are providing some direct results and some useful insights through various ML and DL approaches with the observed predictions and accuracy levels but still, we can revise these models with additional parameter tuning in the context of features for specific recommendations and predictions on the stock market data.…”
Section: Literature Reviewmentioning
confidence: 99%